EMPATHY AMONG PHYSICIANS IN TRAINING AT THE UNIVERSITY HOSPITAL IBN SINA LITERATURE REVIEW AND CROSS SECTIONAL STUDY - Nour El Houda EL FILALI (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2022)
Keywords: Empathy, Empathy related factors, Jefferson Scale of Empathy, Physicians in training, Morocco Introduction Empathy is a key component of medical professionalism. Our study aimed to evaluate empathy and explore its related factors among the physicians in training at the university hospital IBN SINA. Method We conducted a cross sectional study, both descriptive and analytic, between March and July 2019 through an online survey. We collected personal and professional characteristics. We used standardized scales to evaluate Empathy (JSE), quality of life (SF-12) and satisfaction with life (SWLS). The statistical analysis was carried out in Jamovi Statistics. Results We included 103 physicians in training, 69.9% of which were women. The JSE mean score for the total sample was 96.9 (SD=13.4, range=64-135). Cronbach's coefficient ' for the JSE was 0.76. In the multivariate analysis, male gender ('=9.7; p<0.001), higher socio-economic status ('=6.7; p=0.02) and altruistic motivation ('=4.2; p=0.01) were significant predictors of higher empathy levels. On the other hand, working long hours was negatively linked to empathy ('=-4.1; p=0.006). Additionally, we could not detect any association between empathy and the quality of life of the physicians in training. Conclusion Our results highlighted some empathy related factors among the physicians in training. Further research is necessary to investigate these factors in order to implement targeted measures for education and training.
Keywords: Empathy; Empathy related factors; Jefferson scale of empathy; Physicians in training; Morocco